Iron and steel - Hosford, William F.; Cambridge eBooks (Cambridge : Cambridge University Press, 2012)
This book is intended both as a resource for engineers and as an introduction to the layman about our most important metal system. After an introduction that deals with the history and refining of iron and steel, the rest of the book examines their physical properties and metallurgy. To elaborate on the importance of iron and steel, we can refer to the fact that modern civilization as we know it would not be possible without it. Steel is essential in the machinery necessary for manufacturing that meets our needs. Even the words themselves have come to suggest strength. Phrases such as 'iron willed', 'iron fisted', 'iron clad', 'iron curtain' and 'pumping iron' imply strength. A 'steely glance' is a stern look. 'A heart of steel' refers to a very hard demeanor. The Russian dictator, Stalin (which means steel in Russian), chose the name to invoke fear in those under him.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Iron -- History; Steel -- History; Iron -- Metallurgy; Steel -- Metallurgy; Electronic books